[Five Cal Poly men on a bike] (1965)
Photo of five men on motorbike or motorcycle. From left to right: Dave Bigge, Tom Paddock, George Conger, Dennis Jennings, and Rich Duncan. Published in the El Mustang from October 15, 1965 pg. 2 alongside article titled "Five-man squad leads game spirit." A yell leading squad, coordinating the rooting section and keeping spirit running constantly. Also printed in the 1966 El Rodeo pg. 124 under title "Let us have spirit."